2015
DOI: 10.1016/j.sbspro.2015.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Urban Regeneration: GIS and Hedonic Pricing Method in Determining the Value of Green Space in Housing Area

Abstract: This paper explores a framework that combines Geographic information System (GIS) with Hedonic pricing method in improving the analysis and determining the value of green spaces with housing prices in Subang Jaya, Malaysia. The previous study found that proposed combination between GIS and Hedonic pricing method for the same purpose has not been fully explored particularly in Malaysia. Findings show the proposed combined method leads to an improved understanding and representation of urban dynamics and regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Estimates of the economic values or amenity benefits of urban parks and public open spaces have emerged recently [6]; [7]; [8]; [9]; [10]; [11] and [12]. At the first stage, implicit prices for different housing characteristics are estimated with formula given above [8].…”
Section: Methodsmentioning
confidence: 99%
“…Estimates of the economic values or amenity benefits of urban parks and public open spaces have emerged recently [6]; [7]; [8]; [9]; [10]; [11] and [12]. At the first stage, implicit prices for different housing characteristics are estimated with formula given above [8].…”
Section: Methodsmentioning
confidence: 99%
“…The regression model holds dependent variables constant and measures values of independent variables (Noor et al 2015). Regression model indicates, how much property changes by changing in each characteristic of variables through the coefficient values of each characteristic.…”
Section: Regression Model and Property Valuesmentioning
confidence: 99%
“…The pervious literature found that combination of GIS with regression, fully explored the neighborhood amenities, distance base land values provide the evidence in numerical formwork (Noor et al 2015), Where GIS is technique applied for implementation of locational dataset of environmental attributes (Ligus and Peternek 2016). GIS is widely used for handling of spatial data in urban developmental projects, decision making and policies (Pedro et al 2019).…”
Section: Regression Model and Property Valuesmentioning
confidence: 99%
“…1% increase in the size of common area relates with a 0.01% increase in property price. (Veie & Panduro, 2013) Urban green spaces have a positive impact on the property values and this represents a "capitalization" of park land into increased property values of proximate land owners (Noor, Asmawi, & Abdullah, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%